2020
DOI: 10.1056/nejmoa1900236
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal B Vaccine and Meningococcal Carriage in Adolescents in Australia

Abstract: BACKGROUND The meningococcal group B vaccine 4CMenB is a new, recombinant protein-based vaccine that is licensed to protect against invasive group B meningococcal disease. However, its role in preventing transmission and, therefore, inducing population (herd) protection is uncertain. METHODS We used cluster randomization to assign, according to school, students in years 10 to 12 (age, 15 to 18 years) in South Australia to receive 4CMenB vaccination either at baseline (intervention) or at 12 months (control). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 23 publications
7
135
1
3
Order By: Relevance
“…The scarcity of nonpathogenic Neisseria within other bodily niches makes it unlikely that the skin, genital or anorectal site act as an intermediate in this transfer process. As already noted, different types of evidence suggest that pathogenic Neisseria species can be transmitted by kissing [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Our findings support to the idea that the genus Neisseria can be transmitted by kissing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The scarcity of nonpathogenic Neisseria within other bodily niches makes it unlikely that the skin, genital or anorectal site act as an intermediate in this transfer process. As already noted, different types of evidence suggest that pathogenic Neisseria species can be transmitted by kissing [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Our findings support to the idea that the genus Neisseria can be transmitted by kissing.…”
Section: Discussionsupporting
confidence: 90%
“…Concerns around the transmission of commensal Neisseria via kissing have emerged following increasing evidence of this mode of transmission for related bacteria. Several studies have found that kissing is a risk factor for meningococcal disease [9][10][11] or carriage [12][13][14][15] among students. Likewise, N. gonorrhoeae can be readily cultured from saliva [16][17][18], saliva use as a lubricant is a risk factor for rectal gonorrhea [19], kissing [20][21][22] as well as having a main partner with pharyngeal gonorrhea [23] may be risk factors for pharyngeal gonorrhea and a mathematical transmission model showed that oro-oral transmission is essential to generate the actual prevalence of gonorrhea among MSM [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid rise of serogroups W and Y disease prompted all states and territories to fund MenACWY vaccination programs in 2017 and 2018 as an outbreak response . These programs varied but predominantly targeted adolescents aged 15–19 years, aiming to both directly prevent disease and to interrupt community transmission of meningococci through reduced acquisition of nasopharyngeal carriage, which is most prevalent in this age group . Some jurisdictions also implemented time‐limited vaccination programs covering select age groups, from infancy up to older adolescence, to control serogroup W outbreaks.…”
Section: Increased Use Of Quadrivalent Meningococcal Conjugate Vaccinesmentioning
confidence: 99%
“…New data from the UK over 3 years estimate vaccine effectiveness against serogroup B IMD to be 52.7% (95% CI, −33.5 to 83.2) for a two‐dose primary schedule for infants, and 59.1% (95% CI, −31.1 to 87.2) for a two‐dose primary schedule followed by a booster dose at one year . However, Bexsero does not appear to have an impact on nasopharyngeal carriage of serogroup B, which implies that herd immunity (indirect protection in unvaccinated individuals) would be limited or absent despite population‐based vaccination . In addition, for both vaccines, protection against only around three‐quarters of all circulating MenB strains is predicted, based on in vitro assays …”
Section: Meningococcal B Vaccine Use In Australiamentioning
confidence: 99%
See 1 more Smart Citation